Military life : the psychology of serving in peace and combat - Britt, Thomas W., 1966-; Adler, Amy B., 1963-; Castro, Carl Andrew (Westport, Conn. : Praeger Security International, 2006)
With global commitments and combat duty, our armed forces face life-threatening challenges on a daily basis. However, less visible threats also impact the mental health of our military men and women. Experts examine challenges on the battlefield, such as women coming to terms with life after being prisoners of war, or soldiers dealing with mistakenly killing civilians. But life in the armed forces presents less dramatic, daily challenges. Away from the front lines, soldiers have to raise their families, sometimes as single parents. Children have to learn what it's like to be in a military family, and to make sense of war. Gay or lesbian officers cope with a don't ask, don't tell policy. An unprecedented range of contributors--military officers, medical doctors, psychologists, psychiatrists, and professors--take us onto the bases and the battlefields and inside the minds of military personnel who face far greater challenges than most of us ever see in the headlines. These volumes also highlight factors that make members of the military resilient and stable, as well as programs and practices that can ease the psychological burdens of military personnel, families, and children. Readers can better understand how society views our military and military operations, and how each one of us can play a role in supporting our armed forces.
v. 1. MILITARY PERFORMANCE: PART I: FIRST PERSON: What has befallen me? The psychological aftermath of combat / Spencer J. Campbell -- PART II: HUMAN DIMENSIONS OF MILITARY OPERATIONS: Psychological aspects of combat / Robert K. Gifford -- Psychological responses to terrorism / William V. Bobo, Richard T. Keller, Neil Greenberg, Christopher A. Alfonso [and others] -- Psychological operations in combat, peacekeeping, and fighting terrorism / Steven Collins -- PART III: PHYSIOLOGICAL AND COGNITIVE DIMENSIONS OF MILITARY OPERATIONS: Sleep loss: implications for operational effectiveness and current solutions / Nancy J. Wesensten, Gregory Belenky, and Thomas J. Balkin -- Augmented cognition: aiding the soldier in high and low workload environments through closed-loop human-machine interactions / Eric R. Muth, Amy A. Kruse, Adam Hoover, and Dylan Schmorrow -- Decision making and performance under stress / James E. Kriskell, Eduardo Salas, and Joan H. Johnston -- PART IV: SOCIAL AND PERSONALITY DIMENSIONS OF MILITARY OPERATIONS: Morale during military operations: a positive psychology approach / Thomas W. Britt and James M. Dickinson -- Military group cohesion / Guy L. Siebold -- Stress-CARE: an integrated model of individual differences in soldier performance under stress / Robert K. Sinclair and Jennifer S. Tucker -- PART V: FUTURE DIRECTIONS: Military performance common themes and future directions / Thomas W. Britt, Carl Andrew Castro, and Amy B. Adler -- v. 2. OPERATIONAL STRESS: PART I: FIRST PERSON: Kilroy was here: reflection of a psychiatrist in combat / Robert L. Koffman -- PART II: PSYCHOLOGICAL PREPARATION FOR WARFARE: Joining the ranks: the role of indoctrination in transforming civilians to service members / Dennis McGurk, Dave I. Cotting, Thomas W. Britt, and Amy B. Alder -- Scenario-based training: improving military mission performance and adaptability / Eduardo Salas, Heather A. Priest, Katherine A. Wilson, and C. Shawn Burke -- Enhancing mental readiness in military personnel / Megan M. Thompson and Donald R. McCreary -- PART III: PSYCHOLOGICAL DEMANDS DURING AND AFTER DEPLOYMENT: Code of conduct and the psychology of captivity, training, coping, and reintegration / George Steffan, Brendon W. Bluestein, Jerry Orgisseg, Anthony P. Doran, and C.A. Morgan III -- Combat stress control: putting principle into practice / Steve J. Lewis -- Prediction and prevalence of posttraumatic stress disorder among military veterans / Shira Maguen, Michael Suvak, and Brett T. Litz -- PART IV: ORGANIZATIONAL RESPONSES TO PSYCHOLOGICAL CHALLENGES: Human spirituality, resilience, and the role of military chaplains / Thomas C. Waynick, Peter J. Frederich, David M. Scheider, Ronald H. Thomas [and others] -- Toward a liberal theory of military leadership / Carl Andrew Castro, Jeffrey L. Thomas, and Amy B. Adler -- Social climates: drivers of soldier well-being and resilience / Paul D. Bliese -- PART V: FUTURE DIRECTIONS: Operational stress: common themes and future directions / Amy B. Adler, Carl Andrew Castro, and Thomas W. Britt -- v. 3. THE MILITARY FAMILY: PART I: FIRST PERSON: Army wife, army member / Doris Briley Durand -- PART II: CHALLENGES FACING THE MILITARY SPOUSE: Maintaining family resiliency before, during and after military separation / Tina Watson Wiens and Pauline Boss -- Moving military families: the impact of relocation on family well-being, employment, and commitment to the military / Lolita M. Burrell -- Military spouses: coping with the fear and the reality of service member injury and death / Kathleen M. Wright, Lolita M. Burrell, Erica D. Schroeder, and Jeffrey L. Thomas -- PART III: FAMILY DIVERSITY: Single military parents in the new millennium / Michelle L. Kelley -- The challenges and benefits of dual military marriages / Ann H. Huffman and Stephanie C. Payne -- Voices from the backseat: demands of growing up in military families / Morten G. Ender -- PART IV: WORK-FAMILY CONFLICT AMONG MILITARY PERSONNEL: Work-family conflict among military personnel / Gary A. Adams, Steve M. Jex, and Christopher J.L. Cunningham -- Intimate partner violence in the U.S. military: rates, risks, and responses / Julie C. Clark and Stephen C. Messer -- Reducing the negative impact of work-family conflict on military personnel: individual coping strategies and multilevel interventions / Leslie B. Hammer, Jennifer C. Cullen, Gwen C. Marchand, and J. Alison Dezsofi -- PART V: FUTURE DIRECTIONS: The military family: common themes and future directions / Carl Andrew Castro, Amy B. Adler, and Thomas W. Britt -- v. 4. MILITARY CULTURE: PART I: FIRST PERSON: Military culture and values: a personal view / Guy L. Siebold -- PART II: MILITARY VALUES: Culture's consequences in the military / Joseph L. Soeters, Cristine-Rodica Poponete, and Joseph T. Page, Jr. -- From values to performance: it's the journey that changes the traveler / Michael W. Grojean and Jeffrey L. Thomas -- Military courage / Carl Andrew Castro -- PART III: DIVERSE GROUPS: The U.S. reserve component: training strategies for adapting to deployment / Robert A. Wisher and Michael W. Freeman -- The role of women in the military / Penny F. Pierce -- Sexual orientation and military service: prospects for organizational and individual change in the United States / Gregory M. Herek and Aaron Belkin -- PART IV: PERSPECTIVES ON THE MILITARY: Quality of life and subjective well-being among military personnel: an organizational response to the challenge of military life / Michael J. Schwerin -- Life in wartime: real-time news, real-time critique, fighting in the new media environment / Cori E. Dauber -- Poultry and patriotism: attitudes toward the U.S. military / James H. Laurence -- PART V: FUTURE DIRECTIONS: Military culture: common themes and future directions / Thomas W. Britt, Amy B. Adler, and Carl Andrew Castro.
Includes bibliographical references and indexes.
Keywords: United States. -- Army -- Military life; United States. -- Army; Psychology, Military; War -- Psychological aspects; Combat -- Psychological aspects; Peace -- Psychological aspects; Post-traumatic stress disorder; Psychology, Military; Combat Disorders -- psychology; Stress Disorders, Post-Traumatic -- psychology; Military Personnel -- psychology; Stress Disorders, Post-Traumatic; Psychologie militaire; History